THE DEGREE OF ATTENTION IN THE LESSONS OF FIELD TENNIS (Fiep Bulletin - online, 2014)
The objective of the work was to analyze durantes the cognitivo engagement of the pupil the lessons of field tennis. As methodology it was distinguished some 0 variable of the learning process, having characterized a exploratório study. A questionnaire with four questions, divided during four distinct moments of the lesson was used, being these answered a sonorous stimulaton after (whistle), set in motion for the professor. The answers had been analyzed and classified in categories and subcategorias of the attention developed dust Nunes (2004). As he shows had participated to vintes students of the UFRRJ, being ten men and ten women, of the seventh period of the course of licenciatura in physical education. Of answers 22.5% they were on to the motor plan, 20% the psychological aspects, 18.75% the general capacity, 16.25% the comment and evaluation, 6.25% the social aspects, not usable 6.25%, 3.75% the organization of lesson and 2.5% the relative aspects to the task. He concludes yourself that the thought of the pupil is come back to the motor plan during most of the time of the lesson, having as he has also detached the psychological aspects, showing the reality of the tennis, a game that depends intimamente on the physical and psychological part of the pupil until the athlete.
Keywords: Tennis of Field; Engagement Cognitivo; Attention